FROM CSR TO SOCIAL RISK MANAGEMENT– EXPERIENCES FROM MINING MNCS IN ARMENIA - Jacob Taarup Esbensen (European Scientific Journal, ESJ, 2014)
When it comes to social risks multinational companies (MNC) within Mining are one of the most exposed businesses one can imagine. This paper examines how social risk management is practiced through the case of Teghout copper-molybdenum mine in North- Eastern Armenia, supplemented with evidence from other mining MNCs in the country, onsite fieldwork, interviews with key stakeholders, and public available information. This evidence suggest that a standards based social risk management strategy is adopted and that this strategy is based on international Corporate Social Responsibility (CSR) standards and philanthropic activities. However, evidence reveal that local and regional stakeholders, from whom social risk rise, feel disengaged from the process, continue to raise questions about transparency and in some cases actively oppose mining activities and that this is happening despite the use of stakeholder engagement management systems that is promoted through the standard. The implemented social risk management systems are ineffective because they makes the MNC unable to recognise the value of weak ties and fail to build legitimacy and trust with some of the key stakeholders resulting in the creation of more instead of less risk. It is argued that this is caused by MNC’s use of CSR systems focuses on building strong ties, rather than on building trust with the stakeholders that actually pose the biggest social risk.